Effect of fermentation length and concentration of Saccharomyces cerevisiae on the physical and chemical characteristics of gayo arabica coffee I (Coffea arabica L.) - Karina Ulfa; Rita Hayati; Elly Kesumawati; Amhar Abubakar (Agrium, 2026)
Coffee is an agricultural commodity with broad market potential in Indonesia, with Aceh serving as one of the main production centers, particularly for Gayo Arabica coffee, which is known for its high brew quality but still requires improvement through fermentation-based post-harvest processing. This study aims to determine the effects of fermentation duration and Saccharomyces cerevisiae concentration on the physical and chemical characteristics of Gayo I Arabica coffee. The study employed a Randomized Block Design (RBD) with a factorial pattern, involving two factors: fermentation duration (5 hours, 10 hours, and 15 hours) and Saccharomyces cerevisiae concentration (control, 3%, and 4%), with three replicates. Data were analyzed using analysis of variance (ANOVA) and followed by the Honest Significant Differences (HSD) test at the 5% level if a significant effect was found. The parameters observed included yield, moisture content, pH, caffeine content, and L* a* b* color values. The results showed that fermentation duration and Saccharomyces cerevisiae concentration had no significant effect on yield and moisture content, but had a significant effect on pH and a highly significant effect on caffeine content. In general, increasing fermentation duration and Saccharomyces cerevisiae concentration tended to lower the pH and caffeine content of Gayo I Arabica coffee.